2003
DOI: 10.1002/jso.10311
|View full text |Cite
|
Sign up to set email alerts
|

Application of 99mTc labeled chimeric Fab fragments of monoclonal antibody A7 for immunoscintigraphy of pancreatic carcinoma

Abstract: Because the half-life of (99m)Tc is short (6 hr), chA7Fab, which accumulates rapidly in tumors, may be a better carrier of (99m)Tc than intact Mab A7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…While previous studies showed promising results, this study revealed the insufficient accumulation of the antibody-based probe in tumor tissue. However, a similar study successfully utilized a novel full and fragmented antibody (A7) labeled with 125 I and 99m Tc for imaging of nude mice bearing human pancreatic cancer subcutaneous xenograft tumors. , The ratio of radioactivity in tumor tissue, as compared to blood, was significantly higher than that in normal tissue, with the full antibody displaying higher tumor uptake as compared to the antibody fragment.…”
Section: Molecular Imaging Of Pancreatic Cancermentioning
confidence: 99%
“…While previous studies showed promising results, this study revealed the insufficient accumulation of the antibody-based probe in tumor tissue. However, a similar study successfully utilized a novel full and fragmented antibody (A7) labeled with 125 I and 99m Tc for imaging of nude mice bearing human pancreatic cancer subcutaneous xenograft tumors. , The ratio of radioactivity in tumor tissue, as compared to blood, was significantly higher than that in normal tissue, with the full antibody displaying higher tumor uptake as compared to the antibody fragment.…”
Section: Molecular Imaging Of Pancreatic Cancermentioning
confidence: 99%
“…Then, the effect of treatment with the 131 I-labeled chimeric anti-VEGFR2 Fab was determined. To our knowledge, these observations were seldom made in previous studies 19 42 43 that reported the anti-tumor role of radionuclide labeled mAbs.…”
Section: Discussionmentioning
confidence: 77%
“…Others have also examined the application of mAbs to target and provide in vivo imaging of pancreatic cancers, mostly as xenografts in athymic nude mice, although a few have been studied in clinical trials as well (31)(32)(33)(34)(35). While it is difficult to compare all of these previous studies, for the most part radiolabeled whole-IgG has been used, with the result that the highest tumor/blood ratios occurred between 72 and 96 hours postinjection and were in the range of 2:1 to 10:1; in other words, similar to the results we obtained with radiolabeled PAM4 whole-IgG.…”
Section: Discussionmentioning
confidence: 99%